Analisis Penentuan Infrastruktur Prioritas pada Kawasan Kumuh Lingkungan Kerantil Kota Blitar - Ashar Annas; Ria Asih Aryani Soemitro; Eko Budi Santoso (Journal of Civil Engineering, 2018)
Data update from Public Works and Housing Ministry records the existence of slum area in Kerantil District,Blitar City. Blitar City government has tried to address slum problem in that district, but until now slum improvementprograms still not showing significant result. Based on the existing condition, research on priority infrastructure isconducted in Kerantil slum area, Blitar City. The aim of this research is to address proper program response for Kerantilslum area, Blitar City. This research begins with determining factors causing slum in Kerantil slum area usingConfirmatory Factor Analysis. After the factors are determined, infrastructure response priority is determined by meansof Service and quality (servqual) Analysis and Importance Performance Analysis (IPA) by comparing the level ofimportance and performance about infrastructure in slum area based on respondent answer. Several factors causingslum in that area are street infrastructure, drainage infrastructure, water infrastructure, waste infrastructure, buildinginfrastructure, fire protection infrastructure, and green open space infrastructure. The other factors are government role,social, economy, society, and legality. The prioritized infrastructure in Kerantil slum area are waste infrastructure, fireprotection infrastructure, and green open space infrastructure.